The Intersectional Discrimination of Main Character in the Movie “Self Made” Inspired by the Life of Madam C.J Walker (2020) - Pradana, Ami; Andriani, Periska; Febrianti, Mariska (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This research analyze the forms of Intersectional discrimination experienced by the main character in the movie “Self-Made” inspired by the life Madam CJ Walker. Using Kimberle Crenshaw’s theory of intersectionality, this research show how discrimination based on race, gender, social class and sexuality interact and influence the main character’s experience. It is a qualitative study using the observation method. The results explore the moral messages that can be drawn from Madam C.J Walker’s struggle, highlighting the importance of resilience, solidarity between women and rejection of discriminatory beauty standards. This research is expected to raise awareness about discrimination issues and support the strengthening of women’s position, especially among minority communities.